Fabrication and characterization of Ceramic Porcelain tiles - Shamini Muniandy (Universiti Malaysia Perlis, 2008)
Fabrication of ceramic tiles requires detailed attention on the processing parameters such as raw material size and weight percentage, forming and drying process, and sintering temperature. The scope of the project is to study the final product properties with variation in the composition percentage and sintering temperature. This project employs hydraulic powder pressing as primary forming method of compound A, B and C where bar shaped green body was produced. Sintering were conducted in three different temperatures which were at 1200°C, 1300°C and 1400°C for 3 hours at heating rate 5°C/min. The resulting body then analyzed to study the final property of the compounds as function of sintering temperature. Morphology studies were conducted using image analyzer. Meanwhile, the mechanical and physical testing includes particle size analysis, density and porosity study, linear shrinkage study, energy dispersive spectrometry (SEM/EDX) analysis, and modulus of rupture and compression test were done. These analyses have provided the information that pores coarsening has occurred at 1300°C which in turn have produced low mechanical properties. From these studies, mostly all the samples has showed better physical and mechanical properties at 1200°C indicating that 1200°C as the optimum temperature for all the samples. This indicates the small variation of silica would change the properties of the tiles.